2007
DOI: 10.1364/oe.15.011564
|View full text |Cite
|
Sign up to set email alerts
|

Microring-based modulation and demodulation of DPSK signal

Abstract: Ultra-small modulator and demodulator for 10 Gb/s differential phase-shift-keying (DPSK), using silicon-based microrings, are proposed. A single-waveguide microring modulator with over-coupling between ring and waveguide generates a DPSK signal, while a double-waveguide microring filter enables balanced DPSK detection. These modulator and demodulator are characterized. A trade-off between pattern dependence of the Duobinary signal and alternate-mark inversion signal power in demodulator design is discussed. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 15 publications
1
59
0
Order By: Relevance
“…However, for drop port demodulation, the AWG improves the receiver sensitivity by about 3 dB, and around 0.5 dB power penalty is further introduced by the crosstalk. As there is a trade off between the performance of the demodulated AMI and DB signals [13], it is found that the MRR with Q value of 6700 associated with the AWG, lead to similar receiver sensitivities for both through and drop port demodulations.…”
Section: Wavelength Detuning Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…However, for drop port demodulation, the AWG improves the receiver sensitivity by about 3 dB, and around 0.5 dB power penalty is further introduced by the crosstalk. As there is a trade off between the performance of the demodulated AMI and DB signals [13], it is found that the MRR with Q value of 6700 associated with the AWG, lead to similar receiver sensitivities for both through and drop port demodulations.…”
Section: Wavelength Detuning Tolerancementioning
confidence: 99%
“…and are the roundtrip phase shift and field transmission coefficients along the ring waveguide, respectively. NRZ-DPSK signals can be demodulated by the MRR, resulting in the generation of alternate-mark inversion (AMI) and duobinary (DB) signals [13] at the through and drop ports, respectively. Thanks to the periodic nature of the frequency response of the MRR, simultaneous multiple WDM NRZ-DPSK demodulation can be achieved by tuning the carrier wavelength of each channel so that it coincides with one of the notches of the through transfer function.…”
Section: A Principlementioning
confidence: 99%
See 1 more Smart Citation
“…The principle of NRZ-DPSK demodulation is to use the through transmission of a MRR to convert phase modulation to amplitude-modulation [6]. To achieve a Pol-D MRR-based demodulator, a novel PSR is designed, as shown in Fig.…”
Section: Polarization Splitter and Rotatormentioning
confidence: 99%
“…Various types of DPSK demodulators, including delay interferometers [2], optical bandpass filters [3], a birefringent fiber loop [4], or a single silicon wire [5] have been demonstrated. Recently, the use of silicon microring resonators (MRRs) has been proposed and demonstrated for ultra-compact DPSK demodulation [6,7]. The use of such devices as multi-channel wavelength division multiplexing (WDM) non return-to-zero DPSK (NRZ-DPSK) demodulators has also been demonstrated [8].…”
Section: Introductionmentioning
confidence: 99%